Stroke prevention in atrial fibrillation changes after dabigatran availability in China: The GLORIA‐AF registry - Changsheng Ma; Lionel Riou França; Shihai Lu; Hans‐Christoph Diener; Sergio J. Dubner; Jonathan L. Halperin; Qiang Li; Miney Paquette; Christine Teutsch; Menno V. Huisman; Gregory Y. H. Lip; Kenneth J. Rothman; et al. (Journal of Arrhythmia, 2020)
Abstract Background Until the approval of dabigatran etexilate, treatment choices for stroke prevention in patients with atrial fibrillation (AF) were vitamin K antagonists (VKAs) or antiplatelet drugs. This analysis explored whether availability of non‐vitamin K antagonist oral anticoagulants post‐dabigatran approval was associated with changing treatment patterns in China. Methods Global Registry on Long‐Term Oral Antithrombotic Treatment in Patients with Atrial Fibrillation (GLORIA‐AF) collected data on antithrombotic therapy choices for patients with newly diagnosed nonvalvular AF at risk for stroke. In China, enrollment in phase 1 (before dabigatran approval) and phase 2 (after dabigatran approval) occurred from 2011 to 2013 and 2013 to 2014, respectively. Analyses were restricted to sites within China that contributed patients to both phases. The weighted average of the site‐specific results was estimated for standardization. Sensitivity analyses used multiple regression. Results Thirteen sites participated in both phase 1 (419 patients) and phase 2 (276 patients), 76.1% and 16.0% were known to be at high risk for stroke (CHA2DS2‐VASc ≥2) and bleeding (HAS‐BLED ≥3); 55.5% were male. In phase 1, 16.7%, 61.6%, and 21.7% of patients were prescribed oral anticoagulants (OACs), antiplatelet agents, and no treatment, respectively. Respective proportions were 26.4%, 40.6%, and 33.0% in phase 2. The absolute increase in the site‐standardized proportion of patients prescribed OACs after dabigatran availability was 9.9% (95% confidence interval [CI]: 3.7%‐16.0%). There was a standardized 17.3% (95% CI: −24.3% to −10.4%) absolute decrease in antiplatelet agent use. Conclusions There was an increase in OAC and decrease in antiplatelet agent prescription since dabigatran availability in China. However, a large proportion of AF patients at risk for stroke remained untreated.